Age‐related differences in oligodendrogenesis across the dorsal‐ventral axis of the mouse hippocampus. Issue 8 (29th April 2014) - Yamada, Jun; Jinno, Shozo
ABSTRACT Oligodendrocyte precursor cells (OPCs) continue to divide and generate new oligodendrocytes (OLs) in the healthy adult brain. Although recent studies have indicated that adult oligodendrogenesis may be vital for the maintenance of normal brain function, the significance of adult oligodendrogenesis in brain aging remains unclear. In this study, we report a stereological estimation of age‐related oligodendrogenesis changes in the mouse hippocampus: the dorsal subdivision is related to learning and memory, while the ventral subdivision is involved in emotional behaviors. To identify OPCs and OLs, we used a set of molecular markers, OL lineage transcription factor (Olig2) and platelet‐derived growth factor receptor‐alpha (PDGFαR). Intracellular dye injection shows that PDGFαR+/Olig2+ cells and PDGFαR−/Olig2+ cells can be defined as OPCs and OLs, respectively. In the dorsal Ammon's horn, the numbers of OPCs decreased with age, while those of OLs remained unchanged during aging. In the ventral Ammon's horn, the numbers of OPCs and OLs generally decreased with age. Bromodeoxyuridine (BrdU) fate‐tracing analysis revealed that the numbers of BrdU+ mitotic OPCs in the Ammon's horn remained unchanged during aging in both the dorsal and ventral subdivisions. Unexpectedly, the numbers of BrdU+ newly generated OLs increased with age in the dorsal Ammon's horn, but remained unchanged in the ventral Ammon's horn. Together, the numbers of OLs in the dorsal Ammon's horn may be maintained during aging by increased survival of adult born OLs, while the numbers of OLs in the ventral Ammon's horn may be reduced with age due to the lack of such compensatory mechanisms. These observations provide new insight into the involvement of adult oligodendrogenesis in age‐related changes in the structure and function of the hippocampus. © 2014 Wiley Periodicals, Inc.